Arctic National Wildlife Refuge (ANWR) : Legislative Actions Through the 108th Congress. (U.S. Congressional Research., 2005)
Reviews legislative history of the Arctic National Wildlife Refuge (ANWR) in northeastern Alaska, 1957-2004, focusing on legislation in the 107th and 108th Congress addressing energy development and preservation in the ANWR. Covers environmental direction, Federal and native lands, revenue disposition, natural gas pipeline, project labor agreements, oil export restrictions, National Environmental Policy Act compliance, refuge-allowed activities, judicial review, special areas, and non-development options.